BMI, leisure-time physical activity, and physical fitness in adults in China: results from a series of national surveys, 2000–14. Issue 6 (June 2016) - Tian, Ye; Jiang, Chongmin; Wang, Mei; Cai, Rui; Zhang, Yanfeng; He, Zihong; Wang, Huan; Wu, Dongming; Wang, Fubaihui; Liu, Xin; He, Zhongtao; An, Ping; et al.
Summary: Background: Obesity, physical inactivity, and reduced physical fitness contribute to the rising burden of chronic diseases in China. We investigated these factors in Chinese adults over a 14-year period (2000–14) using data from randomised national surveys. Methods: We did four national surveys in 2000, 2005, 2010, and 2014 among Chinese adults aged 20–59 years. We used BMI to assess underweight (<18·5 kg/m 2 ), overweight (≥23·0 to <27·5 kg/m 2 ), and obesity (≥27·5 kg/m 2 ). Central obesity was defined as a waist circumference greater than 90 cm in men and greater than 85 cm in women. We assessed leisure-time physical activity (LTPA) by whether or not participants had completed the recommended minimum 150 min of moderate or 75 min of vigorous exercise per week. Indices for assessment of physical fitness were forced vital capacity, resting heart rate, hand grip strength, sit and reach distance, and time standing on one leg. Findings: 151 656 (78%) of 193 440 adults responded to the survey in 2000, 163 386 (84%) in 2005, 154 931 (80%) in 2010, and 146 703 (76%) in 2014. The prevalence of obesity increased from 8·6% in 2000, to 10·3% in 2005, 12·2% in 2010, and 12·9% in 2014 (estimated increase 0·32% per year, 95% CI 0·30–0·33; p<0·0001). The equivalent estimates were 37·4%, 39·2%, 40·7%, and 41·2% for overweight (estimated increase 0·27% per year, 95% CI 0·25–0·30; p<0·0001) and 13·9%, 18·3%, 22·1%, and 24·9% for central obesity (estimated increase 0·78% per year, 0·76–0·80; p<0·0001). The prevalence of overweight, obesity, and central obesity increased with age (all p<0·0001) and was higher in men than in women (all p<0·0001). We noted a simultaneous decrease in the prevalence of underweight (estimated decrease of 0·06% per year, 95% CI 0·04–0·07; p<0·0001). The proportion of adults meeting the minimum LTPA recommendation increased over time (17·2% in 2000, 18·1% in 2005, and 22·8% in 2014), with the estimated prevalence change per year being 0·33% (95% CI 0·24–0·42; p<0·0001) for underweight people, 0·50% (0·47–0·53; p<0·0001) for normal-weight people, 0·37% (0·34–0·40; p<0·0001) for overweight people, and 0·06% (0·00–0·13; p=0·044) for obese people. We noted deteriorations over time in all measures of physical fitness in normal-weight adults (all p<0·0001), apart from resting heart rate (p=0·69). Interpretation: Despite increased participation in LTPA, we noted increases in overweight or obesity and a decrease in physical fitness in Chinese adults. Continued nationwide interventions are needed to promote physical activity and other healthy lifestyle behaviours in China. Funding: National Physical Fitness Surveillance Center and Ministry of Science and Technology of the People's Republic of China.